Advanced Miasmatic Approach in Ante Natal Care - Multi Faceted Homoepathy - Mitali Teraiya (International Journal of Biomedical Innovations and Engineering, 2025)
Homeopathy and pregnancy care? Looks challenging? The structural deformities investigation in modern medicine is an unforeseen combination of a physical, mental breakdown of pregnant lady, resulting an immediate call for effective therapy of the lady and family. The female-being the pivot, her health in pregnancy marks great responsibility for an Altruistic homeopath. The advanced miasmatic lens in antenatal care magnifies the role of multifaceted homeopathy. Such type of synergistic efforts raise the standards of practicing systems, fostering healthier future generations. The application of miasmatic treatment not only addresses the root cause of underlying issues but also ensures the physical and emotional well-being of the expectant mother. A combination of individualized remedies, diet recommendations, and lifestyle changes helps strengthen the overall constitution. Moreover, advanced homeopathic practices have demonstrated significant potential in preventing complications, managing symptoms, and ensuring the delivery of a healthy child. This comprehensive approach reinforces the significance of holistic care in pregnancy management.
Keywords: Ante-Natal Care; Maternal health; Miasmatic approach; Modern medicine; Preventive care